2002
DOI: 10.1258/0956462021924721
|View full text |Cite
|
Sign up to set email alerts
|

Does bar-based, peer-led sexual health promotion have a community-level effect amongst gay men in Scotland?

Abstract: This paper evaluates the effectiveness of a bar-based, peer-led community-level intervention to promote sexual health amongst gay men. The intervention consisted of peer education within bars, gay specific genitourinary medicine (GUM) services and a free-phone hotline. Data were collected at baseline (1996) and at follow-up (1999) in gay bars in Glasgow (intervention city) and Edinburgh (control city). During the intervention peer educators interacted with 1484 men and new clients increased at the gay specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 11 publications
0
73
0
Order By: Relevance
“…Despite sustaining the programme for 18 months, the critical mass required for diffusion was not established and, as a result, the intervention made no signi cant impact on gay men's risk behaviour. A recent report from a peer education project in Scotland found that even where diffusion does occur, this does not necessarily lead to a reduction in high risk sexual behaviour at a community level (Flowers et al, 2002). Our experience suggests that a model of peer education shown to be effective in one country may not be directly transferable to another and may need to be modi ed before its introduction into the UK.…”
Section: Discussionmentioning
confidence: 71%
“…Despite sustaining the programme for 18 months, the critical mass required for diffusion was not established and, as a result, the intervention made no signi cant impact on gay men's risk behaviour. A recent report from a peer education project in Scotland found that even where diffusion does occur, this does not necessarily lead to a reduction in high risk sexual behaviour at a community level (Flowers et al, 2002). Our experience suggests that a model of peer education shown to be effective in one country may not be directly transferable to another and may need to be modi ed before its introduction into the UK.…”
Section: Discussionmentioning
confidence: 71%
“…MSM gave a sense that they would have tested had they been further encouraged, an important missed opportunity. Missed opportunities in HIV testing, in both primary and secondary care, are widely recognised (Stekler & Golden, 2009 (Kelly et al, 1997;Elford et al, 2002;Flowers et al, 2002;).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, extant research does not explore the social function of PSEs other than to document that it exists; we know little about those cruisers who exploit PSEs' social functions, nor why they choose these locations over other gay spaces. Capitalizing on these structures, health promoters could explore peer education amongst cruisers, similar to the community mobilization models which successfully improved sexual health behaviors amongst gay men who use U.S. and U.K. commercial gay venues (Kegeles, Hays, Pollack, & Coates, 1999;Kelly et al, 1997;Elford, Bolding, & Sherr, 2001a;Flowers, Hart, Williamson, Frankis, & Der, 2002). Moreover, PSEs are likely to provide health promoters' with access to men who do not use commercial gay venues, such as socially disadvantaged men without the fiscal means to access commercial venues, or other MSM whose identity and anonymity may be challenged by the use of the gay scene .…”
Section: Outreach Work and Pse Sexual Culturesmentioning
confidence: 99%